(3GdJeQjfGJ GdMOjKI aj cQI GdbOes - (3YHO Gddg eMeO(B, (3geGes ((3GdEScfOQjI(B;(3GdEScfOQjI(B:s (3eDSSI YGde GdQjGVI ddfTQ(B;(3OGQ GdhaGA dOfjG GdWHGYI(B,s, 2017)
(3JfGhd gPG GdcJGH ehVhY GdJeQjfGJ GdMOjKI aj cQI GdbOe , hjgOa Gdi JMSjf COGA GdLQj HGdcQI aj cQI GdbOe hPdc ef NdGd hVY JeQjfGJ habG deHOC GdbUhQ GdPGJj hGdJYQa Ydi fJjLI JCKjQgG Ydi COGA GdLQj HGdcQI ddeLehYI GdJLQjHjI, GVGaI Gdi hVY JeQjfGJ habG deHOC GdbUhQ GdPGJj hGdJYQa Ydi fJjLI JCKjQgG Ydi HYV GdeJZjQGJ GdHjhejcGfjcjI GdNGUI HegGQI GdLQj HGdcQI ddeLehYI GdJLQjHjI (B.s
(3bGFeI GdCTcGd hGdLOGhd U(B. 184 s
Keywords: (3GdJOQjH GdQjGVjs; (3GdJeQjfGJ GdMOjKIs; (3cQI GdbOes